Melioidosis prostatic abscess: clinical presentation and imaging findings - MR, Razali; Abdul Rashid, Amran; How, Soon Hin; TH, Ng; Che Ahmad, Aminudin; Ab Rahman, Jamalludin (Faculty of Medicine, International Islamic University Malaysia, 2008)
Melioidosis, an infection caused by Burkholderia pseudomallei is endemic in South East Asia and Northern Australia. It can affect many organs in the body such as lung, liver, spleen, bone, prostate, brain and soft tissues. Objective: This study aims to detect the presence of prostatic abscess in patients with a positive blood culture for Burkholderia pseudomallei with computed tomography (CT) of the abdomen and pelvis and to correlate it with the clinical presentation. Materials and Methods: This is a prospective observational study conducted in all melioidosis patients who had CT scan of the abdomen and pelvis. The location and size of any focal lesions seen on CT were recorded. Clinical data such as fever and urinary symptoms were also recorded. Results: 15 patients had CT scan of the abdomen and pelvis. Five patients were diagnosed to have prostatic abscess. Out of the five patients, only two had urinary symptoms. The other three had prolonged high grade fever without any urinary symptoms. Conclusions: Melioidosis prostatic abscess is not uncommon in patients with positive blood culture of Burkholderia Pseudomallei (33% in this series). Most patients do not present with any urinary symptoms.